Osseointegrated total hip replacement connected to a lower limb prosthesis: a proof-of-concept study with three cases. Issue 1 (December 2016) - Khemka, Aditya; FarajAllah, Chalak; Lord, Sarah; Bosley, Belinda; Al Muderis, Munjed
Abstract Background Osseointegrated implants are a suitable alternative for prosthetic attachment in individuals with a transfemoral amputation, who are unable to wear a socket. However, the small bone-implant contact area, reduced muscular leverage, and osteoporosis contraindicate osseointegrated implant use in transfemoral amputees with osteoporosis and a short residuum. We report on the feasibility of combining total hip replacement (THR) with an osseointegrated implant for prosthetic attachment. Methods We retrospectively reviewed the cases of three transfemoral amputees who underwent osseointegration with THR between 2013 and 2014. In a two-stage procedure, a custom-made femoral prosthesis was connected to a THR with a modular revision stem and a stoma was created. Clinical outcomes were assessed at baseline and 1.5–2.5-year follow-up using standard measures of health-related quality of life, ambulation, and activity levels including the Short Form-36 (SF-36), Questionnaire for Transfemoral Amputees (Q-TFA), Timed Up and Go test, and 6-min walk test. Results Patient age ranged from 35 to 65 years. There were no major adverse events, but there was one case of superficial infection. All patients showed improved Q-TFA and SF-36 scores. Two patients who were wheelchair-bound at baseline became community ambulators, and the third patient exhibited improved ambulation. Conclusions This study demonstrated the feasibility of combining a THR with an osseointegrated implant in transfemoral amputees.